(untitled) (UNIZIK Journal of Marketing, 2024)
The main objective of this paper was to examine the effect self regulation and corporate branding among selected firm in food and beverage South East of Nigeria. The research design was survey research design. The population of the study was all the registered food and beverage firms in Nigeria with operational base as South Eastern Nigeria. Available records from Nigeria Directory of statistics show that there are ninety-five (95) registered food and beverage firms in South Eastern Nigeria. The study adopted the total population of the study as the sample size because it was relatively small. Judgmental sampling technique which is a non- probability sampling technique was used in the study because of the nature of the respondents. The source of data for this work was primary. Data was collected through self-administered copies of structured questionnaire. Data collected were analyzed using multiple regression analysis. The findings showed that quality assurance systems, codes of ethics, internal and external markets dispute resolution schemes and accreditation standards have significant effects on corporate branding the implication of the result is that organizations must implement compliance strategy such as quality assurance systems, codes of ethics, an effective market dispute resolution scheme and adherence to accreditation standards of corporate operation in corporate operation in order to build corporate brand.